2016
DOI: 10.1186/s13071-016-1628-9
|View full text |Cite
|
Sign up to set email alerts
|

Thelazia callipaeda in wild carnivores from Romania: new host and geographical records

Abstract: BackgroundThelazia callipaeda is a vector-borne zoonotic nematode parasitizing the conjunctival sac of domestic and wild carnivores, rabbits and humans, with a vast distribution in Asia and the former Soviet Union. In Europe, the nematode has an emerging trend, being reported in Italy, France, Switzerland, Germany, Spain, Portugal, Bosnia and Herzegovina, Croatia, Romania, Greece and Serbia, with human cases known in Italy, France, Spain, Serbia and Croatia. In Romania, the infection was so far reported only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 21 publications
1
22
0
Order By: Relevance
“…The spirurid nematode Thelazia callipaeda (Spirurida: Thelaziidae) is the major etiological agent of ocular thelaziosis [ 1 ]. This worm can parasitize the conjunctival sac of domestic and wild carnivores and humans, causing conjunctivitis, lacrimation and itchiness, and even blindness [ 2 , 3 ]. The parasite is transmitted by a drosophilid insect of the genus Phortica (Diptera, Drosophilidae), that feeds on the lachrymal secretions of mammals [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The spirurid nematode Thelazia callipaeda (Spirurida: Thelaziidae) is the major etiological agent of ocular thelaziosis [ 1 ]. This worm can parasitize the conjunctival sac of domestic and wild carnivores and humans, causing conjunctivitis, lacrimation and itchiness, and even blindness [ 2 , 3 ]. The parasite is transmitted by a drosophilid insect of the genus Phortica (Diptera, Drosophilidae), that feeds on the lachrymal secretions of mammals [ 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Based on their relationships to known Thelazia hosts in Europe, 2 potential hosts in New York State include coyotes, red fox, gray fox, black bear, raccoon, mink, least weasel, striped skunk, cottontail rabbit, and snowshoe hare. 16 Therefore, the role of wildlife (e.g., foxes, jackal, hares, and wolves) 2,17,18 as reservoirs of T. callipaeda should be assessed, considering that the infection most likely establishes in wildlife before spreading to dogs and other domestic animals. 2 In Europe, eyeworm infection is often reported in foxes, most likely because of the more frequent exposure of wild carnivores to Phortica spp.…”
mentioning
confidence: 99%
“…The occurrence of this spirurid nematode species has also been reported in Eastern Europe. The adult worms have been found in one or both eyes of dogs, cats, foxes and/or humans in Croatia [ 7 , 21 ], Serbia [ 8 , 22 , 35 ], Romania [ 23 , 24 ], Bosnia and Herzegovina [ 21 ], Bulgaria [ 25 ] and Slovakia [ 26 , 27 ]. Before this study, only a single canine ocular thelaziosis was reported in Hungary [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Considering the first cases of canine thelaziosis found close to the southern and northern borders of Hungary, we assume that T. callipaeda may have been introduced recently or arrived in the country several years ago by infected host(s) from neighbouring countries where the occurrence of this nematode species has been reported [ 21 , 22 , 26 , 27 ]. Thelazia callipaeda seems more likely to be transmitted to Hungary by wild carnivores, which play an important role in the sylvatic cycle of this eyeworm species [ 3 , 21 , 24 , 37 ]. It has been reported that the specimens of this nematode were found in the eyes of red foxes in the northern regions of Balkans [ 21 ] and in the southern part of Slovakia close to the Hungarian border [ 27 ] (Fig.…”
Section: Discussionmentioning
confidence: 99%